Becoming the evidence-based manager [electronic resource] : making the science of management work for you - Latham, Gary P. (Davies-Black ; Society for Human Resource Management, 2009)
Lays out management advice in a logical linear framework that ties directly to the natural progression of management skills throughout the employee life cycle. This title features six general lessons of management that guide readers on what they should and sometimes shouldn't be doing to become an evidence-based manager.